Ekofeminisme Batak Toba: Pembacaan lintas tekstual Kejadian 1 dan kosmologi si Boru Deang Parujar - Sipahutar, Roy Charly H. P.; Tampubolon, Rinto; Pasaribu, Andar Gunawan (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Ecofeminism positions women and nature as having a strong passion so that the suffering experienced by nature as a result of global multi-systems is also women's suffering. Efforts to achieve gender and ecological justice are usually carried out by Western feminists who focus on liberal, radical, and socialist models of feminism, which do not always seem to be relevant to contexts in other parts of the world, especially Indonesia. Related to this, this research aims to construct contextual ecofeminist ideas for Batak Toba women in Tapanuli whose nature is being injured. This research uses a cross-textual hermeneutic approach to dialogue Genesis 1 with the cosmological myth Si Boru Deang Parujar. The results of constructive dialogue show no hierarchical domination between men, women, and nature. The order of creation is only realized when humans and nature can live in harmony and harmony. Batak Toba women are the